2015
DOI: 10.1016/j.jamda.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Context on Best Practice Use by Care Aides in Residential Long-Term Care Settings

Abstract: Our study suggests that context plays an important role in care aides' use of best practices in nursing homes. Individual characteristics played a more prominent role than contextual factors in predicting conceptual use of best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 61 publications
2
60
0
1
Order By: Relevance
“…A few (e.g., culture, social capital, structural and electronic resources, and slack time) were significant across the relationship between both IRU and CRU and pain outcomes. Squires et al [13] reported that there were more elements of organizational context that predicted CRU ( n  = 6) versus IRU ( n  = 1) while Estabrooks et al [15] found almost queal numbers of ACT elementat influenced IRU ( n  = 4) versus CRU ( n  = 3) Some elements of organizational context (e.g., culture, social capital, structural and electronic resources, and slack time) appear to operate in similar ways for both IRU and CRU in relation to the caregiver process or best practice outcomes (e.g. pain assessment using a valid measure).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few (e.g., culture, social capital, structural and electronic resources, and slack time) were significant across the relationship between both IRU and CRU and pain outcomes. Squires et al [13] reported that there were more elements of organizational context that predicted CRU ( n  = 6) versus IRU ( n  = 1) while Estabrooks et al [15] found almost queal numbers of ACT elementat influenced IRU ( n  = 4) versus CRU ( n  = 3) Some elements of organizational context (e.g., culture, social capital, structural and electronic resources, and slack time) appear to operate in similar ways for both IRU and CRU in relation to the caregiver process or best practice outcomes (e.g. pain assessment using a valid measure).…”
Section: Discussionmentioning
confidence: 99%
“…IRU (i.e., direct use of research) was measured using one item on a five point scale where 1 = never use and 5 = almost always use [15]. The IRU item has been shown to be acceptable to respondents [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using hierarchical linear models, the authors also demonstrated that the ACT pediatric acute care (Estabrooks et al, 2011c) and the ACT LTC (Estabrooks et al, 2011a) were able to discriminate between different care units. Most recent evidence based on multi-level models suggests that the ACT concepts are significant predictors of research utilization (Squires et al, 2013a; Estabrooks et al, 2015b) as well as resident outcomes (Estabrooks et al, 2015a; relation to other variables validity evidence).…”
Section: Methodsmentioning
confidence: 99%
“…The Canadian research team was able to demonstrate that more favorable organizational context as assessed by the ACT is positively associated with staff outcomes such as use of best practice (Estabrooks et al, 2015b), lower burnout (Estabrooks et al, 2012), and a better trajectory of resident symptom burden in the last 12 months of life (Estabrooks et al, 2015a). Comparable German research tools were unavailable, therefore we translated the Canadian tools into German, adapted them to the context of German LTC settings, and studied their psychometric properties.…”
Section: Introductionmentioning
confidence: 99%